AGRICULTURAL DECENTRALIZATION IN ROMANIA - ROMANIAS AGRICULTURAL ORGANIZATION OF CHAMBERS - Bogdan, Bazgă (Economics of Agriculture, 2012)
In this article are theoretical and real explanations on Romanian agriculture decentralization process and the importance of creating and organized of the Agriculture Chamber. The need to be more presents in all the Romanian regions in order to develop the agriculture consultancy and all the factors that influence them. It also shows the status of national consultancy level, illustrated by a series of specific indicators and trends of their evolution. Finally, make some assessments about the prospects for Agriculture Chamber in our country.